Кон Henri Atlan et Roger Pol-Droit, Chemins qui mènent ailleurs. Dialogues philosophiques: Për Henri Atlan et Roger Pol-Droit, Chemins qui mènent ailleurs. Dialogues philosophiques - Sekulovski, Jordančo; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон Henri Atlan et Roger Pol-Droit, Chemins qui mènent ailleurs. Dialogues philosophiques Title (Albanian): Për Henri Atlan et Roger Pol-Droit, Chemins qui mènent ailleurs. Dialogues philosophiques Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 175-176 Page Count: 2 Citation (Macedonian): Јорданчо Секуловски, „Кон Henri Atlan et Roger Pol-Droit, Chemins qui mènent ailleurs. Dialogues philosophiques“, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 175-176. Citation (Albanian): Jordančo Sekulovski, „Për Henri Atlan et Roger Pol-Droit, Chemins qui mènent ailleurs. Dialogues philosophiques“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 175-176.